TRUST MEMEDIASI ONLINE CUSTOMER REVIEW DAN RATING TERHADAP MINAT BELI MELALUI MARTKETPLACE SHOPEE - Nidia Agustin Wibowo; Koko Safitri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study used quantitative data and the data collection method used in this study was a questionnaire using a Likert scale. The population used in this study were STIE Sampit students who used Shopee as a place to shop online. While the sample in this study amounted to 75 respondents and used a sampling technique based on accidental sampling, namely based on the coincidence of anyone who met and made a purchase at the shopee marketplace. The results of this study indicate that (1) online customer reviews have a significant effect on purchase intention with a t statistic value of 2.664 (2) online customer reviews have a significant effect on trust with a t statistical value of 4.709 (3) online customer ratings have no effect on purchase intentions with a t value statistic 1.028 (4) online customer rating has a significant effect on trust with a t statistic value of 4.555 (5) trust has a significant effect on purchase intention with a t statistic value of 2.346 (6) trust mediates online customer review of purchase intention with a t statistic value of 2.029 (7) trust mediates online customer rating of purchase intention with a statistical t value of 2.019. The R Square result of buying interest is 0.393 indicating that the research model is classified as moderate and means that online customer reviews, online customer ratings, and trust together contribute to buying interest of 39.9% and the rest is influenced by other variables outside of this study.